Edentulism in Saudi Arabia and associated factors - Haroub, Anas Omar; Khormi, Abdullah Abdu; Yankesar, Rawan Ahmad; Alhumaid, Shaden Abdullah; Aleissa, Mohammad Ibrahim; Alotheem, Lubna Saleh; Alsharif, Hussain Nayef; Alghamdi, Khalid Abdulaziz; Alateeq, Hassan Hamoud; Alshehri, Ali Saeed; Alaidarous, Alaa Mohammad (International Journal Of Community Medicine And Public Health, 2021)
The epidemiology of edentulism is different across the different communities and the prevalence rates are also significantly different and it can be affected by various factors. There have been many investigations that reported the prevalence rates of edentulism across the different countries globally. However, not many investigations were published in Saudi Arabia and the published ones also report different findings. In the present study, we have reviewed the current studies in the literature to investigate the prevalence of edentulism and associated factors in Saudi Arabia. Our results indicated that the reported rates were conflicting among the different reports across the Kingdom and some of these rates are lower than other rates that were reported in some countries but higher than others also. Therefore, further nationwide research was still needed to formulate better evidence and help draw adequate interventions for the most vulnerable groups. Age, gender, educational levels, regional residency, socioeconomic status, depression and diabetes have all been reported to be correlated with edentulism. The prevalence of the condition has been reported to be highest among older age groups, while evidence is contradicting about the difference between both genders. Therefore, targeting vulnerable populations with early interventions can reduce the incidence rates and enhance the quality of life among these populations.